Shutter (2014), volume 1 ebook Wanderlost. - Keatinge, Joe (Shutter (2014), 2014)
JOE KEATINGE (GLORY, TECH JACKET, Adventures of Superman) teams up with artist extraordinaire LEILA DEL DUCA for her Image Comics debut in the very first collection of their all-new ongoing series combining the urban fantasy of Fables and the globe-spanning adventure of Y: The Last Man. Kate Kristopher, once the most famous explorer of an Earth far more fantastic than the one we know, is forced to return to the adventurous life she left behind when a family secret threatens to destroy everything she spent her life protecting. Collects SHUTTER #1-6.. Author: Joe Keatinge. Illustrator: Leila Del Duca . 2014 Joe Keatinge & Leila Del Duca.